Standardisasi Signboard, Rambu, dan Marka Area Jalan Sisi Darat di BLU UPBU Kelas I Aji Pangeran Tumenggung Pranoto - Samarinda - Wijaya, Satria Danu; Kardi; Lestary, Dwi (Jurnal Ground Handling, 2025)
Aji Pangeran Tumenggung Pranoto Airport in Samarinda is a vital infrastructure supporting mobility and the economy in East Kalimantan. However, issues were identified regarding the non-compliance of signboards, traffic signs, and road markings in the landside area with both national and international standards. This study aims to analyze the existing condition of these facilities and assess their conformity with regulations such as the Indonesian National Standard (SNI) and Ministerial Regulations. A descriptive qualitative approach was employed using field observations, interviews, and document analysis. The findings revealed visibility issues at night, signs obstructed by trees, lack of road markings, and inadequate signboards in terminal areas. Recommendations include applying retro-reflective materials to signs, adding and repositioning signs and road markings, and improving information on terminal signboard. This research is expected to contribute to enhancing safety, operational efficiency, and passenger convenience in the landside area of the airport, and serve as a basis for technical policy development.